Coal-tar pitch-based lithium ion battery electrode and preparation method and application thereof
Patent Information
- Application Number
- CN202611067879.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-27
AI Technical Summary
虽然该正极材料在0.2C、5C下的放电容量分别达到了148mAhg-1、104mAhg-1,且在1C下经历100次循环后,放电容量保留为99.2%,但该方案的着眼点主要在于正极材料,并未对硬碳材料的锂离子扩散动力学进行深入研究和优化
(1)本发明改善了锂离子在硬碳材料中扩散动力学缓慢的问题,通过在硬碳材料基体中加入二氧化硅和二茂铁来原位生长碳纳米管来提供大量缺陷位点,从而形成丰富的活性位点以供锂离子的存储,同时扩大层间距促进锂离子的扩散动力学,CTP-SiO2@Fe的储锂机制遵循“吸附-嵌入”理论,即Li+首先嵌入碳层之间,随后进一步在局部平行碳层围成的纳米孔隙中填充或聚集,这是电池可逆容量的主要来源,且此过程通常分阶段进行;部分Li+以原子或簇的形式,吸附在负极材料的表面、端面、边缘或缺陷处。
Smart Images

Figure CN122991997A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, and relates to a coal tar pitch-based lithium-ion battery electrode, its preparation method and application. Background Technology
[0002] Lithium-ion batteries mainly consist of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode material is a crucial factor in improving the capacity and cycle performance of lithium-ion batteries, and its performance has become a key determinant of battery performance. Therefore, the selection of negative electrode materials plays a vital role.
[0003] In the field of lithium-ion batteries, hard carbon materials have attracted widespread attention due to their excellent electrochemical performance, but the slow diffusion kinetics of lithium ions in hard carbon materials limit their application in high-power-density lithium-ion batteries.
[0004] For example, patent CN119361662A discloses a carbon-based composite material with an internal mesh structure and an external carbon layer coating. This material improves the discharge capacity and cycle performance of the electrode material by growing carbon nanotubes on the surface of silicon powder and coating them with a silica layer and a hard carbon layer. However, this technical solution does not fully address the diffusion kinetics of lithium ions in hard carbon materials, and the ion diffusion kinetics of the electrode material still need further optimization.
[0005] Patent CN102227022A proposes a lithium iron phosphate / carbon / carbon nanotube composite cathode material with lithium vacancies, using pitch as the carbon source, and improving the rate performance and cycle performance of the material through in-situ synthesis. Although this cathode material achieves a discharge capacity of 148 mAh g⁻¹ at 0.2C and 5C, it is not yet fully developed. -1 104mAhg -1 Furthermore, after 100 cycles at 1C, the discharge capacity remains at 99.2%. However, this scheme mainly focuses on the cathode material and does not conduct in-depth research and optimization on the lithium-ion diffusion kinetics of hard carbon materials. Summary of the Invention
[0006] The purpose of this invention is to overcome the problem of slow diffusion kinetics of lithium ions in hard carbon materials, thereby providing a coal tar pitch-based lithium-ion battery electrode, its preparation method, and its application.
[0007] The objective of this invention can be achieved through the following technical solutions: One of the technical solutions of the present invention is to provide a method for preparing a coal tar pitch-based lithium-ion battery electrode, comprising the following steps: S1. Coal tar pitch, silicon source and iron source catalyst are mixed to obtain a precursor. The precursor is carbonized at high temperature under an inert gas atmosphere, and then acid washed, water washed and dried to obtain the active material. S2. Mix the active material obtained in step S1 with the conductive agent and binder to obtain the electrode slurry; S3. The electrode slurry obtained in step S2 is coated onto a carbon-coated copper foil and dried to obtain a lithium-ion battery electrode.
[0008] In some specific embodiments, in step S1, the silicon source is selected from any one of silicon dioxide, nano-silicon, silane, and silicic acid, and the iron source catalyst is selected from any one of ferrocene, ferric acetate, ferric oxide, and ferric citrate.
[0009] In some specific implementations, in step S1, the mass ratio of coal tar pitch, silicon source, and iron source is 7:4:(0.5-3).
[0010] In some specific embodiments, the process conditions for high-temperature carbonization in step S1 are: holding at 200-300℃ for 2-4 hours, then heating to 800-1100℃ for 2-8 hours.
[0011] In some specific embodiments, in step S2, the conductive agent is selected from either Ketjen Black or Super P. The adhesive is selected from any one or more of hydroxymethyl cellulose, styrene-butadiene rubber, and polyvinylidene fluoride (PVDF).
[0012] In some specific embodiments, in step S2, the mass ratio of the active material, conductive agent, and binder is 40:5:(5-10).
[0013] In some specific embodiments, in step S3, the loading of active material on the carbon-coated copper foil is 0.8-1.2 mg / cm³. 2 .
[0014] In some specific embodiments, the drying process conditions for step S3 are: vacuum drying at 60-120 °C for 4-24 hours.
[0015] The second technical solution of the present invention is to provide a coal tar pitch-based lithium-ion battery electrode, which is obtained by the preparation method described in one of the above technical solutions.
[0016] The third technical solution of the present invention is to provide an application of the coal tar pitch-based lithium-ion battery electrode as described in the second technical solution above in the preparation of lithium-ion batteries, wherein the coal tar pitch-based lithium-ion battery electrode serves as the negative electrode.
[0017] Compared with the prior art, the present invention has the following advantages: (1) This invention improves the problem of slow lithium-ion diffusion kinetics in hard carbon materials. By adding silica and ferrocene to the hard carbon material matrix to grow carbon nanotubes in situ, a large number of defect sites are provided, thereby forming abundant active sites for lithium-ion storage. At the same time, the interlayer spacing is increased to promote lithium-ion diffusion kinetics. The lithium storage mechanism of CTP-SiO2@Fe follows the "adsorption-intercalation" theory, that is, Li + First, it embeds itself between carbon layers, and then further fills or aggregates in the nanopores formed by locally parallel carbon layers. This is the main source of the battery's reversible capacity, and this process usually occurs in stages; some Li + They adsorb onto the surface, end face, edge, or defects of the negative electrode material in the form of atoms or clusters.
[0018] (2) The lithium-ion battery electrode material prepared by the present invention has active sites and pore structure for lithium-ion storage, which is conducive to efficient electron transfer and ion adsorption. Therefore, it exhibits excellent rate capacity and significant cycle stability in the battery. Attached Figure Description
[0019] Figure 1 Figure 1 shows a scanning electron microscope (SEM) image of CTP (Figure 1); Figure 2 shows a scanning electron microscope (SEM) image of CTP-SiO2@Fe (Figure 2).
[0020] Figure 2 The Raman spectra of CTP-SiO2@Fe and CTP are shown.
[0021] Figure 3 The infrared spectra of CTP-SiO2@Fe and CTP are shown.
[0022] Figure 4 For CTP-SiO2@Fe batteries and CTP batteries at 0.1Ag -1 The initial constant current charge-discharge curves (Figure a). Cycle performance of CTP-SiO2@Fe battery and CTP battery (Figure b). Rate performance of CTP-SiO2@Fe battery and CTP battery (Figure c).
[0023] Figure 5 Figure a shows the CV curves of CTP-SiO2@Fe at different scan rates; Figure b shows the calculated values of CTP-SiO2@Fe; 2 mV s -1 The capacitance contribution of CTP-SiO2@Fe at different scan rates (Figure c, blue area); the proportion of capacitance contribution and diffusion control contribution of CTP-SiO2@Fe at different scan rates (Figure d).
[0024] Figure 6Figure a shows the CV curves of CTP at different scan rates; Figure b shows the calculated b-value of CTP; Figure c shows the proportions of capacitance contribution and diffusion control contribution of CTP at different scan rates; 2 mV s -1 Capacitive contribution of CTP at scan rate (Figure e, blue area).
[0025] Figure 7 EIS spectra of CTP-SiO2@Fe and CTP.
[0026] Figure 8 Figure a shows the cycle performance of CTP-SiO2 and CTP batteries. Figure b shows the rate performance of CTP-SiO2 and CTP batteries. Detailed Implementation
[0027] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0029] Unless otherwise specified, the materials and processes described in the following embodiments or examples are conventional materials and processes used in the art to achieve the corresponding functions.
[0030] Example 1: This embodiment provides a lithium-ion battery electrode material, the preparation method of which includes the following steps: (1) First, weigh 3.5 g of coal tar pitch (CTP) and grind it in a mortar for 15 min. After thorough grinding, disperse it by ultrasonication for 15 min to obtain a pitch dispersion. Then, weigh 2 g of SiO2 powder and add it to 10 ml of anhydrous ethanol. Disperse it by ultrasonication for 15 min to obtain a SiO2 suspension. Subsequently, add the obtained SiO2 suspension and 1 g of ferrocene to the previously prepared pitch dispersion and stir continuously for 6 h. Evaporate the mixed solution in an oil bath at 60 ℃. Finally, dry it in a vacuum oven at 60 ℃ for 12 h. Transfer the material to a ceramic slab and place it in a tube furnace for vapor deposition (CVD) under a nitrogen atmosphere. Hold it at 300 ℃ for 2 h and then heat it to 900 ℃ for 2 h. Place the carbonized product in 1-5 M hydrochloric acid and stir and acid wash for 1-2 h to remove residual iron ions and other impurities. After washing with water and drying, obtain the active material.
[0031] (2) Weigh 200 mg of active material, 25 mg of conductive agent Ketjen black (ECP-600JD), 1250 mg of 1wt% (solid content) binder hydroxymethyl cellulose (CMC2200) and 52.6 mg of 48wt% (solid content) styrene-butadiene rubber (SBR307), grind them and then stir them with a magnetic stirrer for 8 h to form an electrode slurry; (3) Using a coater with a 50 μm surface area, the electrode paste was uniformly coated onto the carbon-coated copper foil, with an active material loading of 1.0 mg / cm³. 2 The composite electrode was obtained, and after vacuum drying at 80 °C for 12 h, a lithium-ion battery electrode (CTP-SiO2@Fe) was obtained, which is the lithium-ion battery electrode of coal tar composite material.
[0032] The prepared CTP-SiO2@Fe was characterized as follows: like Figure 1 Images a and b show scanning electron microscope (SEM) images of CTP-SiO2@Fe and CTP. During the carbonization process, coal tar pitch serves as a precursor, and ferrocene as a catalyst, enabling in-situ growth of carbon nanotubes from the coal tar pitch. The CTP-SiO2@Fe obtained through co-carbonization of coal tar pitch and ferrocene possesses excellent lamellar and spherical structures, as well as grown tubular structures, which effectively promotes ion and electron transport.
[0033] like Figure 2 The Raman spectra shown confirm that CTP-SiO2@Fe exhibits typical D and G peak characteristics. Quantitative analysis of the intensity ratio (ID to GG) of the D peak further confirms this. D / I G To assess the material defect concentration, CTP-SiO2@Fe was compared to CTP. D / I G The value increased from 0.57 to 0.90, indicating a significant increase in the defect concentration of the treated material. This enhanced defect concentration is beneficial to Li + Rapid adsorption.
[0034] like Figure 3 The infrared spectrum shown above uses the CTP-SiO2@Fe prepared above as an example of CTP-SiO2@Fe and CTP at approximately 1600 cm⁻¹. -1 and 800 cm -1 Both retained obvious benzene ring skeletal vibrations and CH characteristic absorption peaks, indicating that the recombination process did not destroy the original organic framework structure of CTP. The most significant difference between the two lies in the absorption peak of CTP-SiO2@Fe at approximately 1100 cm⁻¹. -1A very strong broad absorption peak appeared at the point, which is attributed to the antisymmetric stretching vibration of the Si-O-Si bond, indicating that SiO2 was successfully coated on the CTP surface. At the same time, the change in absorption intensity in the -OH region also reflects the introduction of silanol groups.
[0035] The prepared negative electrode sheet is then assembled into a lithium-ion battery, following these steps: Assemble the battery in the following order: positive electrode shell, negative electrode sheet (CTP-SiO2@Fe), separator, lithium sheet, gasket, spring sheet, and negative electrode shell. Add 6-8 drops of lithium battery electrolyte (LB-014), and press the battery into a tablet to obtain a button cell. Set the pressure of the tablet press to 1000 kg / cm². 2 After 5 seconds, the button cell battery is installed, and the manufactured battery is obtained, which is denoted as CTP-SiO2@Fe battery.
[0036] As a control group, the negative electrode was replaced with CTP, and the resulting button cell was denoted as a CTP cell.
[0037] The lithium storage performance of CTP-SiO2@Fe batteries and CTP batteries was studied using cyclic voltammetry (CV).
[0038] like Figure 4 As shown in Figure a, the CTP-SiO2@Fe battery operates at 0.1 A g. -1 The first-week discharge and charge capacities were 640.28 and 280.99 mAh g, respectively. -1 CTP batteries, on the other hand, operate at 0.1A g. -1 The discharge and charge capacities in the first week were 742.42 and 463.68 mAh g, respectively. -1 Their initial coulomb efficiencies (ICE) were 43.88% and 62.42%, respectively.
[0039] like Figure 4 As shown in b, the CTP-SiO2@Fe battery was subjected to 0.05 A·g -1 After activation by a current density of 0.2 A·g -1 At a current density of 425.68 mAh g⁻¹, after 105 cycles, the discharge and charge specific capacities of CTP-SiO₂@Fe were 425.68 mAh g⁻¹. -1 and 421.57 mAh g -1 Its capacity retention rate is 95.5%, while the CTP battery, after 0.05 A·g -1 After activation by a current density of 0.2 A·g -1 At the specified current density, after 105 cycles, the discharge and charge specific capacities of the CTP were 98.5 mAh g⁻¹. -1 and 98.54 mAh g-1 Its capacity retention rate is only 33.2%.
[0040] like Figure 4 As shown in Figure c, by comparing the rate performance of different samples in lithium-ion batteries, it was found that the CTP-SiO2@Fe battery has the best rate performance in the range of 0.1-5.0 A g. -1 It exhibits the best rate performance at current densities, with capacities of 501.91, 454.12, 335.44, 275.51, 131, and 35.83 mAh·g, respectively. -1 This is significantly higher than the CTP batteries at the same current density, which are 301.52, 195.43, 155.33, 94.42, 41.28, and 5.14 mAh·g⁻¹. -1 .
[0041] like Figure 5 As shown in Figure a, the lithium storage kinetics of CTP-SiO2@Fe were studied. Its CV curves at different scan rates in a lithium-ion battery showed no significant shift in peak position with increasing scan rate, indicating a very weak polarization effect. The b-values of the anode and cathode peaks of CTP-SiO2@Fe, calculated using the formula, were 0.433 and 0.709, respectively. Figure 5 (b) This illustrates the rapid energy storage mechanism in lithium-ion batteries dominated by surface capacitance behavior. The capacitance contribution percentage at different scan rates is calculated using the formula: at 2.0 mV·s -1 The capacitance contribution rate reached 67%, and increased from 24% to 87% with increasing scan rate. Figure 5 (c~d) demonstrates that CTP-SiO2@Fe maintains excellent kinetic performance even at high scan rates.
[0042] like Figure 6 As shown in Figure a, the lithium storage kinetics of CTP were studied, and its CV curves at different scan rates in a lithium-ion battery showed that the b-values of the CTP anode peak and cathode peak were 0.403 and 0.743, respectively. Figure 6 (b) indicates that it possesses lithium storage characteristics similar to CTP-SiO2@Fe. At 2.0 mV s -1 The capacitance contribution rate reached 35%, and the capacitance contribution rate also increased from 15% to 47% with the scan rate. Figure 6 (c~d), but the capacitance contribution at each scan rate was lower than that of CTP-SiO2@Fe, confirming that CTP-SiO2@Fe has more outstanding rate performance.
[0043] like Figure 7As shown, the electron transport rates inside the two electrodes were further analyzed by electrochemical impedance spectroscopy (EIS). The semi-circular diameter in the high-frequency region shows that the charge transfer resistance (Rct) of CTP-SiO2@Fe is only 344.1Ω, which is significantly lower than that of CTP (536.2Ω), which is conducive to rapid electron transport.
[0044] Comparative Example 1: This comparative example provides a lithium-ion battery electrode material, the preparation method of which includes the following steps: (1) First, weigh 3.5 g of coal tar pitch and grind it in a mortar for 15 min. After thorough grinding, disperse it by ultrasonication for 15 min to obtain a pitch dispersion. Then, weigh 2 g of SiO2 powder and add it to 10 ml of anhydrous ethanol. Disperse it by ultrasonication for 15 min to obtain a SiO2 suspension. Finally, dry it in a vacuum oven at 60℃ for 12 hours. Transfer the material to a ceramic slab and place it in a tube furnace. Perform vapor deposition (CVD) under a nitrogen atmosphere. Hold the material at 300℃ for 2 h and then heat it to 900℃ for 2 h. Place the carbonized product in 1-5M hydrochloric acid for 1-2 h to remove other impurities remaining in the product. After washing with water and drying, obtain the active material.
[0045] (2) Weigh 200 mg of active material, 25 mg of conductive agent Ketjen black (ECP-600JD), 1250 mg of 1wt% (solid content) binder hydroxymethyl cellulose (CMC2200) and 52.6 mg of 48wt% (solid content) styrene-butadiene rubber (SBR307), grind them and then stir them with a magnetic stirrer for 8 h to form an electrode slurry; (3) Using a coater with a 50 μm surface area, the electrode paste was uniformly coated onto the carbon-coated copper foil, with an active material loading of 1.0 mg / cm³. 2 The composite electrode was obtained, and after vacuum drying at 80 °C for 12 h, a lithium-ion battery electrode (CTP-SiO2) was obtained, which is the lithium-ion battery electrode of coal tar pitch composite material.
[0046] The CTP-SiO2 prepared above is used as the negative electrode for assembling lithium-ion batteries, and the steps are as follows: Assemble the battery in the following order: positive electrode shell, negative electrode sheet (CTP-SiO2), separator, lithium sheet, gasket, spring sheet, and negative electrode shell. Add 6-8 drops of lithium battery electrolyte (LB-014), and press the battery into a tablet to obtain a button cell. Set the pressure of the tablet press to 1000 kg / cm². 2 After 5 seconds, the button cell battery can be installed, and the manufactured battery is obtained, which is called CTP-SiO2 battery.
[0047] As a control group, the negative electrode was replaced with CTP, and the resulting button cell was denoted as a CTP cell.
[0048] The lithium storage performance of CTP-SiO2 batteries and CTP batteries was studied using constant current charge-discharge test (GCD).
[0049] like Figure 8 As shown in Figure a, the first-week discharge and charge capacities of the CTP-SiO2 battery are 779.88 mAh g, respectively. -1 and 420.14 mAh g -1 Its initial coulombic efficiency (ICE) was 53.87%, while that of the CTP battery was 742.42 and 463.68 mAh g, respectively. -1 Its initial coulombic efficiency (ICE) was 62.42%. The CTP-SiO2 cell underwent a process of 0.05 A·g... -1 After activation by a current density of 0.2 A·g -1 At a current density of [value missing], the discharge and charge specific capacities of CTP-SiO2 after 105 cycles were 44.93 mAh g⁻¹. -1 and 45.09 mAh g -1 Its capacity retention rate is 21.9%, and the CTP battery has a capacity retention rate of 0.05 A·g. -1 After activation by a current density of 0.2 A·g -1 At the specified current density, after 105 cycles, the discharge and charge specific capacities of the CTP were 98.5 mAh g⁻¹. -1 and 98.54 mAh g -1 Its capacity retention rate is 33.2%, which is lower than the 95.5% capacity retention rate of the CTP-SiO2@Fe battery of this invention.
[0050] like Figure 8 As shown in b, by comparing the rate performance of different samples in lithium-ion batteries, it was found that the CTP-SiO2 battery has the best rate performance in the range of 0.1-5.0 A g. -1 It exhibits rate performance at current densities of 306.24, 270.17, 172.03, 104.26, 50.67, and 5.28 mAh·g, respectively. -1 This is higher than the CTP batteries at the same current density, which are 301.52, 195.43, 155.33, 94.42, 41.28, and 5.14 mAh·g. -1 However, it is significantly lower than the CTP-SiO2@Fe batteries of this invention at the same current density, which are 501.91, 454.12, 335.44, 275.51, 131, and 35.83 mAh·g. -1 .
[0051] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a coal tar pitch-based lithium-ion battery electrode, characterized in that, Includes the following steps: S1. Coal tar pitch, silicon source and iron source catalyst are mixed to obtain a precursor. The precursor is carbonized at high temperature under an inert gas atmosphere, and then acid washed, water washed and dried to obtain the active material. S2. Mix the active material obtained in step S1 with the conductive agent and binder to obtain the electrode slurry; S3. The electrode slurry obtained in step S2 is coated onto a carbon-coated copper foil and dried to obtain a lithium-ion battery electrode.
2. The method for preparing a coal tar pitch-based lithium-ion battery electrode according to claim 1, characterized in that, In step S1, the silicon source is selected from any one of silicon dioxide, nano-silicon, silane, and silicic acid, and the iron source catalyst is selected from any one of ferrocene, ferric acetate, ferric oxide, and ferric citrate.
3. The method for preparing a coal tar pitch-based lithium-ion battery electrode according to claim 1, characterized in that, In step S1, the mass ratio of coal tar pitch, silicon source, and iron source is 7:4:(0.5-3).
4. The method for preparing a coal tar pitch-based lithium-ion battery electrode according to claim 1, characterized in that, In step S1, the high-temperature carbonization process conditions are as follows: hold at 200-300℃ for 2-4 hours, then raise the temperature to 800-1100℃ and react for 2-8 hours.
5. The method for preparing a coal tar pitch-based lithium-ion battery electrode according to claim 1, characterized in that, In step S2, the conductive agent is selected from either Ketjen Black or Super P. The adhesive is selected from any one or more of hydroxymethyl cellulose, styrene-butadiene rubber, and polyvinylidene fluoride (PVDF).
6. The method for preparing a coal tar pitch-based lithium-ion battery electrode according to claim 1, characterized in that, In step S2, the mass ratio of active material, conductive agent, and binder is 40:5:(5-10).
7. The method for preparing a coal tar pitch-based lithium-ion battery electrode according to claim 1, characterized in that, In step S3, the loading of active material on the carbon-coated copper foil is 0.8-1.2 mg / cm³. 2 .
8. The method for preparing a coal tar pitch-based lithium-ion battery electrode according to claim 1, characterized in that, In step S3, the drying process conditions are: vacuum drying at 60-120 ℃ for 4 h-24 h.
9. A coal tar pitch-based lithium-ion battery electrode, characterized in that, It is prepared by any of the preparation methods described in claims 1 to 8.
10. The application of the coal tar pitch-based lithium-ion battery electrode as described in claim 9 in the preparation of lithium-ion batteries, characterized in that, The coal tar-based lithium-ion battery electrode serves as the negative electrode.
Citation Information
Patent Citations
Li2FeSiO4 anode material for lithium ion battery and preparation method thereof
CN102227022A
Carbon-based composite material for lithium battery as well as preparation method and application of carbon-based composite material
CN119361662A